Mechanochemical ring-opening metathesis polymerization: development, scope, and mechano-exclusive polymer synthesis - Lee, Gue Seon; Lee, Hyo Won; Lee, Hyun Sub; Do, Taeyang; Do, Jean-Louis; Lim, Jeewoo; Peterson, Gregory, I; Friscic, Tomislav; Kim, Jeung Gon (Royal Society of Chemistry, 2022)
Ruthenium-alkylidene initiated ring-opening metathesis polymerization has been realized under solid-state conditions by employing a mechanochemical ball milling method. This method promotes greenness and broadens the scope to include mechano-exclusive products. The carbene- and pyridine-based Grubbs 3(rd)-generation complex outperformed other catalysts and maintained similar mechanistic features of solution-phase reactions. High-speed ball milling provides sufficient mixing and energy to the solid reaction mixture, which is composed of an initiator and monomers, to minimize or eliminate the use of solvents. Therefore, the solubility and miscibility of monomers and Ru-initiators are not limiting factors in solid-state ball milling. A wide variety of solid monomers, including ionomers, fluorous monomers, and macromonomers, were successfully polymerized under ball milling conditions. Importantly, direct copolymerization of immiscible (ionic/hydrophobic) monomers exemplifies the synthesis of mechano-exclusive polymers that are difficult to make using traditional solution procedures. Finally, the addition of a small amount of a liquid additive (i.e., liquid-assisted grinding) minimized chain-degradation, enabling high-molecular-weight polymer synthesis.